Regulation of ROS–NF‐κB axis by tuna backbone derived peptide ameliorates inflammation in necrotizing enterocolitis. Issue 8 (17th January 2019) - Zhang, Le; Fan, Jianfeng; He, Jingya; Chen, Wenjuan; Jin, Weilai; Zhu, Yuting; Sun, Haibing; Li, Yawen; Shi, Yingzuo; Jing, Yulei; Wang, Xiaolei; Han, Shuping; et al.
Abstract: Necrotizing enterocolitis (NEC) is the most common life‐threatening gastrointestinal disease encountered in the premature infant. It has been shown that the intercellular reactive oxygen species (ROS) generation activated by lipopolysaccharide involved in the nuclear factor kappa B (NF‐κB) activation and pathogenesis of NEC. Here, we report that an antioxidant peptide from tuna backbone protein (APTBP) reduces the inflammatory cytokines transcription and release. APTBP directly scavenges the free radical through 1, 1‐diphenyl‐2‐picrylhydrazyl (DPPH) and 2‐phenyl‐4, 4, 5, 5‐tetramethylimidazoline‐1‐oxyl 3‐oxide (PTIO) assay. In addition, APTBP reduces the intracellular ROS level, exhibiting an antioxidant activity within cells. Remarkably, gavage with APTBP attenuates the phenotype of NEC in the mice model. Mechanically, the NF‐κB activation, together with the expression of inflammatory cytokines are decreased significantly when intracellular ROS are eliminated by APTBP. Therefore, our findings demonstrated that an antioxidant peptide, APTBP, ameliorates inflammation in NEC through attenuating ROS–NF‐κB axis. Abstract : In this study, we show evidence that antioxidant peptide from tuna backbone protein reduced intestinal inflammation by scavenging reactive oxygen species and attenuating nuclear factor kappa B mediated release of proinflammatory cytokines in necrotizing enterocolitis.